EFFECTIVENESS OF ONLINE VIDEO GAMES IN CINEMATHERAPY TO IMPROVE STUDENT'S PROSOCIAL BEHAVIOR - Khoiri, Muhammad Hilmy; Muhid, Abdul (EDUCATIONE, 2023)
The problem discussed in this Literature Review is the effectiveness of online video games in cinematherapy to improve students' prosocial behavior. Students as agents of change and the nation's next generation have big responsibilities in the future. Instilling positive social interaction behavior in the form of prosocial can provide benefits both for individuals and for the community environment where students take shelter. The need for prosocial behavior is of course also directly proportional to the need for special strategies in the form of treatment to increase prosocial behavior. Online video games, which are currently quite loved by teenagers, are known to improve a person's skills, including prosocial behavior. The atmosphere of online games that are formed in such a way for players to carry out prosocial activities can inspire players to also carry out prosocial behavior in the real world. Films in Cinematherapy which also display various symbolic modeling messages can also convey various implied information about prosocial behavior. The combination of online video games and cinematherapy to provide various scenes and symbolic messages to the players can increase prosocial behavior for students.